CHARACTERISTICS OF CONFIRMED PREGNANT MOTHERS WITH COVID-19 AND NEONATAL OUTCOMES - Rachmayanti, Erma; Wisnubroto, Cakrabumi (Fakultas Kedokteran Universitas Islam Al-Azhar, 2022)
COVID-19 is a disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A pregnant woman is vulnerable to health problems, particularly infectious diseases. This study aimed to provide an overview of the characteristics of pregnant women with COVID-19 and their neonatal outcomes. A descriptive study with a retrospective approach was carried out by tracing the medical records of the pregnant women with COVID-19. The information collected was the maternal age, gestational age, parity, types of delivery, pregnancy complications, clinical symptoms, chest radiography, newborn weight, baby's APGAR score, and neonatal complications. In a retrospective search, 53 pregnant women were confirmed to have COVID-19. Most of them (79.2%) were in the 21 to 35 years age group, had given birth more than once (69.8%), term pregnancy (84.9%), without pregnancy complications (52.8%), was asymptomatic (58.5%), and had a normal chest radiograph (81.1%). The percentage of mothers who gave birth by cesarean section was 54.7%, while vaginal delivery was 45.3%. Fifty-two (98.1%) babies were born alive, and one baby died in utero with gastroschisis (1.9%). Three infants (5.7%) died after delivery, and four infants confirmed COVID-19 (7.5%). There was no increase in neonatal morbidity and mortality among confirmed pregnant women with COVID-19. COVID-19 has not been proven vertical transmission from mother to baby. Keywords: COVID-19; Pregnant Women; Neonates.